KONTRIBUSI USAHATANI SALAK TERHADAP PENDAPATAN KELUARGA PETANI DI WILAYAH PANGU KECAMATAN RATAHAN TIMUR - Christiani S. Timbulus; Martha M. Sendow; Theodora M. Katiandagho; Jean F.J. Timban (Universitas Sam Ratulangi, 2015)
ABSTRACT Christiani S. Timbulus, 2015. farming contributes to the family income of farmers bark at Pangu Regional District of East Ratahan (under the guidance of Martha M. Sendow, as Chairman, as well as Theodora M. Katiandagho and Jean F. J. Timban as Members). This study aims to analyze the contribution of farm income to the family income of farmers bark barking at Pangu Territory, in 2014. The study was conducted in the region, namely Pangu Pangu village of Parent, Village Pangu Pangu Village One and Two, District East Ratahan Southeast Minahasa District for four months , namely in November 2014 until April 2015, from preparation, data collection, to the preparation of research reports. Data were analyzed using descriptive quantitative contribution formula farmers' income. Results from this study indicate that farm barking contribute to the family income of farmers in the region Pangu. Each for every strata of research which contributes Parent Pangu farm barking in the amount of 78.39%, Pangu 1 with a contribution of 71.06% and Pangu 2 with a contribution of 66.57%. This means farming barking becomes a source of farmers 'income because the value of farmers' income to the total income of the family is very large. Keyword : Contribution, Revenue, Farmer, Farming Bark